Dating and Dating Violence: Social Representations of School Adolescents - Silva, Karla Costa (2022)
This study aimed to analyze the Social Representations of adolescents on dating and dating violence from their social anchors. This is a quantitative-qualitative, descriptive-exploratory study, involving 215 adolescents from public schools located in the city of João Pessoa – Paraíba, aged between 14 and 18 (M=16.16; SD=1.26), predominantly female (60.5%). Participants answered the Free Word Association Technique (FWAT); the Conflict in Adolescent Dating Relationship Inventory (CADRI); and, a sociodemographic questionnaire. Data from the CADRI and sociodemographic characterization were submitted to descriptive analysis, while those from the FWAT to the Correspondence Factor Analysis. Results anchored social objects in the affective, behavioral, psycho-affective, psycho-organic and valorative spheres. Dating was objectified as complicity, fidelity, respect, love, commitment, deception, betrayal, kiss, and fight. While dating violence was objectified as jealousy, disrespect, sadness, quarrel, cowardice, rape, wrong, hate, death and verbal. Keywords: Dating; Violence; Social representations.